Neuroeducational Model in Learning Tahfizh Al-Qur'an: Strengthening Spiritual Literacy in the Era of Digital Disruption - Sahrizal Vahlepi; Zulaika Zulaika; Warissuddin Soleh; Helmun Jamil; Neldi Harianto (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This research develops the Neuroeducation-Based Tahfizh Learning Model (MP-TBN) to strengthen students’ spiritual literacy in the digital era. The model seeks to balance rote memorization with the internalization of Qur’anic values. Employing a Research and Development (R&D) method through the ADDIE framework, the study involved 25 students at Tahfizh Ibadurrahman House, Jambi. Data were collected using observations, interviews, and affective-spiritual questionnaires, then analyzed with qualitative-thematic and quantitative-descriptive approaches. The results show that MP-TBN is built on four pillars: Brain-Based Memorization Strategy (BBMS), Digital Tahfizh Tracker (DTT), Ruhaniyah-Based Reflection (RBR), and Daily Neuro-Murojaah Habit (DNMH). Expert validation confirmed its feasibility, and field trials demonstrated notable improvements: memorization increased from 3.2 to 4.6 juz, reflection from 2.9 to 4.3, focus from 3.1 to 4.5, and spiritual depth from 3.0 to 4.5. Moreover, 90% of participants expressed satisfaction with the model. In conclusion, MP-TBN integrates cognitive, affective, and spiritual dimensions, providing a holistic approach relevant to Tahfizh institutions in addressing contemporary Islamic educational challenges.